(untitled) (Research, Society and Development, 2026)
The Education through Work for Health Program (PET-Saúde) has been standing out as a significant strategy for promoting equity in access to and quality of training for health professionals in Brazil, enabling students to better understand social inequalities and the specific health needs of different groups. The objective of this report was to share the methodology, discussion, and inferred results of this experience, highlighting the importance of promotingequity and the fundamental role of Equity Committees. The questionnaire aimed to evaluate the existence, structure and functioning of the Equity Committees in the municipalities of the Governador Valadares microregion, in addition to identifying possible challenges faced, aiming to identify and understand equity promotion strategies to help strengthen them. The results of the analysis showed that the main limitation faced by the committees is related to the lack of knowledge about their own role and about equity issues, showing that the lack of structured information compromises the effectiveness of these participation spaces. Based on the categorization of the data, three central descriptors were identified: institutional resistance, lack of training on equity and absence of a situational diagnosis. These notes denote the importance of PET-Saúde influence in the construction of alternatives that can assist municipalities, through committees, in promoting equity among healthcare workers.